2022
DOI: 10.1002/jbm.b.35122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leukocyte‐platelet‐rich fibrin in bone healing around dental implants placed in conventional and wide osteotomy sites: A pre‐clinical study

Abstract: Leukocyte‐platelet‐rich fibrin (L‐PRF) has been suggested for gap management for immediate implant placement when the distance is greater than 2 mm. However, there remains a paucity in hierarchically designed research to support this application. The present study aimed to evaluate the effect of L‐PRF on the osseointegration parameters of dental implants placed after conventional osteotomy of surgically created bone defects that simulate post extraction sockets in a canine model after 3, 6, and 12 weeks in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…Thus the opportunity for soft tissue intervention in bone repair has been denied. This justification agrees with the results obtained from the study of Benalcázar et al [ 59 ]; the study demonstrated that before implantation, L-PRF placement within wide osteotomies led to increased early bone growth as compared to unfilled wide osteotomies at the early healing time (three weeks in-vivo). In our study, the delayed placement of implants eliminated the need for scaffolding and physical barriers.…”
Section: Discussionsupporting
confidence: 92%
“…Thus the opportunity for soft tissue intervention in bone repair has been denied. This justification agrees with the results obtained from the study of Benalcázar et al [ 59 ]; the study demonstrated that before implantation, L-PRF placement within wide osteotomies led to increased early bone growth as compared to unfilled wide osteotomies at the early healing time (three weeks in-vivo). In our study, the delayed placement of implants eliminated the need for scaffolding and physical barriers.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, studies that take into consideration the dentin and pulp of extracted teeth subjected to decalcification to fill postextraction sites are not interesting; the shredded dentin continues to progress as part of the bone and presents a cost-free autologous material [42][43][44][45]. Further, in this regard, researchers [46][47][48][49][50][51][52] have paid great attention to platelet concentrates and the different ways of preparing them. The results obtained using platelet concentrates are by far the best, especially for soft tissues and less so for bone.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrin network is responsible for supporting the entire cell distribution in platelet concentrates and providing a membrane property for these blood products [ 24 , 25 , 26 ]. One study [ 16 ] investigated the formation and structure of the fibrin network.…”
Section: Discussionmentioning
confidence: 99%